A Photo Essay on Senegal: Advancing Development and a Pull Backwards by Tradition - Hoeberlein, Caitlin (Consilience, 2013)
Senegal is a country of contradictions. Cultural holdovers from the past battle with the influx of foreign ideas and development strategies. Development in Senegal takes many forms, yet despite the many steps forward in ameliorating living conditions and protecting the environment, traditional practices and perspectives often delay or hinder these advances. This is true in all sectors, including the environment, politics, urban planning, and community development. How the Senegalese harmonize new strategies with traditional perspectives will determine the extent and effectiveness of future development.